First Case of West Nile Fever in a Child in Autonomous Republic of Crimea - N.V. Rymarenko; A.E. Chitakova; E.R. Mazinova; Kh.Sh. Dzhemileva (Zaslavsky O.Yu., 2014)
The article shows a case report of West Nile fever in 11-year-old boy taken from own clinical experience. The duration of the diseases was typical, with fever, meningism, lymphadenitis, hyperemic of facial and chest skin, conjunctivitis, pain in muscles of low extremities.